Waterfowl Censuses on the Mississippi River from St. Louis, Missouri, to Cairo, Illinois; 19 November 1975 through 12 April 1976 - Bellrose, Frank C.; Sanderson, Glen C.; Crompton, Robert (1976)
not peer reviewed Open Restriction set for Item 123045 on 2022-04-12T19:41:15Z with date null by braxton@illinois.edu. Submitted by Susan Braxton (braxton@illinois.edu) on 2022-04-12T19:45:28Z No. of bitstreams: 1 WaterfowlCensusesMississippi19751976.pdf: 8414225 bytes, checksum: 5544f880b62e1100b57d83b4b0368271 (MD5) Made available in DSpace on 2022-04-12T19:45:28Z (GMT). No. of bitstreams: 1 WaterfowlCensusesMississippi19751976.pdf: 8414225 bytes, checksum: 5544f880b62e1100b57d83b4b0368271 (MD5) Previous issue date: 1976-08-10 unpublished Open